PERANAN DAN PERMASALAHAN TEKNOLOGI INFORMASI DAN KOMUNIKASI DALAM PEMBELAJARAN - Harlina, Harlina; Aryani, Novita (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
As we know, times have entered the era of globalization. That opens all the doors and windows of our insights without just going through books, but also through other media. The use of ICT in this era can also improve the quality of education, namely by opening wide access to the access to science and the provision of quality education. With the existence of ICT, the teacher can utilize various supporting facilities that facilitate him in delivering material in the learning process. But in reality there are still many problems that must be corrected in an effort to use ICT in learning such as there are still many teachers and principals who have not been technologically literate, the extent of the Indonesian state so that there are still many areas that have not been touched by electricity especially the internet and the high cost of these ICT tools.